Recycling knowledge among Malaysians towards maintaining clean environment - Krishnan, Devika; Ghazali, Marni; Hj. Md Shahid, Khairiyah; Hamid@Hussain, Shawal Sahid; Hassan, Suziana (Global Academic Excellence (M) Sdn Bhd, 2022)
As Malaysia seeks to present itself as a developed country, the issue of sustainable waste management has emerged as a top priority for policymakers and other relevant parties. Despite the government's efforts, such as the imposition of new regulations and the promotion of privatization, Malaysia continues to trail behind in sustainable waste management techniques, particularly in the field of recycling. The purpose of this study is to determine the relationship of recycling programmes and knowledge towards clean environment in Malaysia. Due to the Covid-19 epidemic, this survey was done through an online form, with a total of 302 respondents. Convenience sampling is chosen because it suits the environment of our study in which it is often readily and easily available. Based on the findings, it is proved that there is no significant and negative relationship between knowledge and recycling programmes (r= 45.955, p= 0.124). The knowledge on recycling programme on clean environment is believed to be poor among Malaysian.